Quantification of polyreactive immunoglobulin G facilitates the diagnosis of autoimmune hepatitis. Issue 1 (5th December 2021) - Taubert, Richard; Engel, Bastian; Diestelhorst, Jana; Hupa‐Breier, Katharina L.; Behrendt, Patrick; Baerlecken, Niklas T.; Sühs, Kurt‐Wolfram; Janik, Maciej K.; Zachou, Kalliopi; Sebode, Marcial; Schramm, Christoph; Londoño, María‐Carlota; et al.
Abstract: Background and Aims: Detection of autoantibodies is a mainstay of diagnosing autoimmune hepatitis (AIH). However, conventional autoantibodies for the workup of AIH lack either sensitivity or specificity, leading to substantial diagnostic uncertainty. We aimed to identify more accurate serological markers of AIH with a protein macroarray. Approach and Results: During the search for more‐precise autoantibodies to distinguish AIH from non‐AIH liver diseases (non‐AIH‐LD), IgG antibodies with binding capacities to many human and foreign proteins were identified with a protein macroarray and confirmed with solid‐phase ELISAs in AIH patients. Subsequently, polyreactive IgG (pIgG) was exemplarily quantified by reactivity against human huntingtin‐interacting protein 1‐related protein in bovine serum albumin blocked ELISA (HIP1R/BSA). The diagnostic fidelity of HIP1R/BSA binding pIgG to diagnose AIH was assessed in a retrospective training, a retrospective multicenter validation, and a prospective validation cohort in cryoconserved samples from 1, 568 adults from 10 centers from eight countries. Reactivity against HIP1R/BSA had a 25% and 14% higher specificity to diagnose AIH than conventional antinuclear and antismooth muscle antibodies, a significantly higher sensitivity than liver kidney microsomal antibodies and antisoluble liver antigen/liver pancreas antigen, and a 12%–20% higher accuracy than conventional autoantibodies. Importantly, HIP1R/BSA reactivity was present in up to 88% of patients with seronegative AIH and in up to 71% of AIH patients with normal IgG levels. Under therapy, pIgG returns to background levels of non‐AIH‐LD. Conclusions: pIgG could be used as a promising marker to improve the diagnostic workup of liver diseases with a higher specificity for AIH compared to conventional autoantibodies and a utility in autoantibody‐negative AIH. Likewise, pIgG could be a major source of assay interference in untreated AIH.